Phylogenomic data yield new and robust insights into the phylogeny and evolution of weevils - Shin, Seunggwan (2018)
The phylogeny and evolution of weevils (the beetle superfamily Curculionoidea) has been extensively studied, but many relationships, especially in the large family Curculionidae (true weevils; > 50,000 species), remain uncertain. We used phylogenomic methods to obtain DNA sequences from 522 protein-coding genes for representatives of all families of weevils and all subfamilies of Curculionidae. Most of our phylogenomic results had strong statistical support, and the inferred relationships were generally congruent with those reported in previous studies, but with some interesting exceptions. Notably, the backbone relationships of the weevil phylogeny were consistently strongly supported, and the former Nemonychidae (pine flower snout beetles) were polyphyletic, with the subfamily Cimberidinae (here elevated to Cimberididae) placed as sister group of all other weevils. The clade comprising the sister families Brentidae (straight-snouted weevils) and Curculionidae was maximally supported and the composition of both families was firmly established. The contributions of substitution modeling, codon usage and/or mutational bias to differences between trees reconstructed from amino acid and nucleotide sequences were explored. A reconstructed timetree for weevils is consistent with a Mesozoic radiation of gymnosperm-associated taxa to form most extant families and diversification of Curculionidae alongside flowering plants - first monocots, then other groups - beginning in the Cretaceous.